Hutan Yang Gundul, di Lereng Gunung Batu Nirwala. Kelurahan Welai Timur, Kalabahi 2023 - Benyamin Oulaana; Melki I. Puling Tang; Petrus Mau Tellu Dony; Benyamin Mailehi; Defi Y. Lekai (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The forest is a large area of ​​land overgrown with trees. Forests are useful in maintaining the balance of the environment for humans. Forests are categorized based on the types of trees present in the forest. There is a teak forest because the majority of trees in the forest are teak. Trees in the forest have many functions including holding back the rate of soil erosion, absorbing carbon dioxide, adding soil nutrients, being able to reduce wind speed and so on. , but it also helps to get a deeper explanation. Forest damage due to illegal logging occurred in East Welai Village, forest damage occurred in forest areas which were mostly planted with teak trees. This also happened in the forest area of ​​the Nirwala Stone Mountain Slopes. The perpetrators of the logging are none other than the local people who live around the forest. In early 2000 the condition of Mount Batu Nirwala was bare without any trees. Natural disasters such as earthquakes began to hit the area around the forest. Drought also occurs even in the rainy season. The water discharge at the springs has decreased. This condition encourages the emergence of awareness of the people who live under the slopes of the mountain to carry out a conservation movement to restore the function of the Nirwala Batu Mountain forest which has been a buffer for the ecosystem for the area beneath it. deforested so that it can restore the function of forest ecosystems such as storing carbon as a source of groundwater reserves, reducing the amount of carbon dioxide, rebuilding wildlife habitat